Spænding, samspil og frisættelse: En undersøgelse af forholdet mellem inkarnation og eskatologi i Grundtvigs salme “Midt iblandt os er Guds Rige” - Schiøler, Aage (Grundtvig-studier, 2008)
Spænding, samspil ogfrisættelse: En undersøgelse afforholdet mellem inkarnation og eskatologi i Grundtvigs salme “ Midt iblandt os er Guds Rige”, 1853 (GS VlIV, 344-345)[Tension, interplay, and release: An analysis of the relation between incarnation and eschatology in Grundtvig 's hymn “ Midt iblandt os er Guds Rige” (The Kingdom of God is in our midst)]By Aage Schiøler The article analyses the hymn’s composition and its vocabulary with special reference to its biblical background and its relation to Christian traditions. Its distinctive character is determined as a suspenseful interplay between a dynamic way of thinking and a meditative mode of expression. In consequence of this interplay, even the hymn’s final statement is marked by openness, not termination.A comparison between the composition of the hymn and the structure of examples from Japanese Haiku-poetry reveals that, although invisible, the Kingdom of God, the hymn’s main topic, is not to be perceived as a mere figment of the brain, the content of which would depend on the reader’s fortuitous ideas or personal preferences. It stands forth as the coordinating fellow player within the total context of the hymn, and as such it is defined as a liberating intervention in human life that opens its basic qualities: faith, hope, and charity, towards the future, as well in communal life as in individual existences. The force and contents of this authentic human existence, as it could be called, are the life and destiny of Jesus from Nazareth. It is seen as carried down through history by means of the preaching of the Gospel, Baptism, and Holy Communion in Christian congregations, exerting influence within communal life, and being accepted by the individual through faith.As the essence of this freedom and openness, The Kingdom of God forms the connexion between incarnation, seen as the crucial, liberating event in history in day-to-day matters in the present time, and eschatology, seen as an incessant, new opening towards the future both in chronological meaning, ‘earthly’, and in existential significance, ‘eternally’.